Updated geostrophic circulation and volume transport from satellite data in the Southern Ocean - Vargas-Alemañy, Juan A.; Vigo, M. Isabel; García-García, David; Zid, Ferdous (Frontiers in Earth Science, 2023)
A geodetic estimation of the Surface Geostrophic Currents (SGC) can be obtained from satellite data by combining Sea Surface Height (SSH) measurements obtained from altimetry missions with geoid data from gravity missions. These SGC serve as a reference for inferring a comprehensive three-dimensional (3D) geostrophy by propagating them downwards using temperature and salinity profiles. In this work, we revisit this problem for the Southern Ocean estimating the 3D geostrophy near full-depth in 41 layers, with a 1º spatial resolution and monthly temporal resolution, covering the 12 years period from 2004 to 2015. We analyze the obtained 3D geostrophy over the Southern Ocean region, where the Antarctic Circumpolar Current (ACC) and its several fronts are clearly depicted, as well as other major currents as the Agulhas Current, the Malvinas Current or the East Australian Current. From the 3D geostrophic currents, we estimate the associated water Volume Transport (VT) as well and present the results for the ACC and the Drake Passage in the context of existing literature. Our analysis yields a mean VT estimate of 15.9 ± 0.1 Sv per 1º cell within the ACC region, and 149.2 ± 2.2 Sv for the Drake Passage ([60.5ºS, 54.5ºS]x[303.5ºE] ). Importantly, our study includes a comprehensive validation of the results. The spatial resolution of our space-data based approach enables us to provide VT estimates for various paths followed in the different in-situ campaigns at the Drake Passage thereby validating our findings. The analysis demonstrates a remarkable agreement across different measurement locations, reconciling the differences in estimates reported from different campaigns. Moreover, we have estimated the barotropic and baroclinic components of the currents and its associated VT.